Isolation of Antifungal Compound Against Phytophthora Infestans from Stellera chamaejasme L. - Shi, G.Y.; Tao, K.; Zhou, W.; Hou, T.P. (Asian Journal of Chemistry, 2013)
Our present investigation was in order to isolate antifungal constituents from the roots of Stellera chamaejasme L., using activity against several phytopathogenic fungi as a lead. Bioactivity guided fractionation of the ethyl acetate extract has led to the isolation of a novel antifungal compound (compound 1), which has exhibited a potent antifungal activity against Phytophthora infestans (EC50 138 mg/L). The antimicrobial activity of this compound against Phytophthora infestans has never been studied before. Its structure was established as chamaechromone on the basis of spectral analysis data, including 1H NMR, 13C NMR and high resolution mass spectrometry.